Notes on certain class of analytic functions with negative coefficients - Shigeyoshi Owa; Tadayuki Sekine; Teruo Yaguchi; Mamoru Nunokawa; Donka Pashkouleva (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to show the extreme points of the class A(n,Bk) consisting of analytic functions with negative coefficients and the support points of the subclass A *(n,Bk) of A(n,Bk).